Prevalence of multi-drug-resistant tuberculosis among human immunodeficiency virus and nonhuman immunodeficiency virus-positive pulmonary tuberculosis patients of two referral hospitals in Southeast Nigeria - Okoro, Chinenye; Ibhawaegbele, Stellamaris; Ezema, Charles; Ezeugwu, Uchechukwu; Igweagu, Chukwuma; Dozie-Nwakile, Ogechukwu (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Introduction: Multidrug-resistant tuberculosis (MDR-TB) is a type of TB that is resistant to the two most effective first-line drugs: rifampicin and isoniazid and it remains a major public health threat, particularly in developing countries. Objectives: To assess the MDR-TB prevalence among human immunodeficiency virus (HIV) and nonHIV positive pulmonary TB patients of two referral hospitals in southeast Nigeria. Materials and Methods: Sputum specimens of individuals presenting with a cough of >2 weeks duration were screened by Ziehl–Neelsen technique for the presence of acid-fast bacilli (AFB). Results: A total of 103 subjects with AFB-positive sputum samples were recruited from the two referral hospitals and HIV-1/2 antibodies were screened using serial algorithm method. The positive sputum samples were subjected to Xpert MTB/RIF assay (GeneXpert®, Cepheid, USA) and cultured on the Lowenstein–Jensen medium for 42 days at 37°C. Drug susceptibility testing was done on the isolates using the nitrate reduction assay. Eighty-three (80.6%) of the isolates were obtained from culture after suspected colonies were subjected to morphological, biochemical, and immunological tests and of the 83 (80.6%) samples analyzed using Xpert MTB/RIF assay 45 (67.2%) were rifampicin-resistant. The prevalence of culture-positive TB was higher in the HIV-negative sub-population (82.02%) when compared with the HIV-positive participants (71.40%). The rate of MDR-TB was high among HIV-positive patients though not statistically significant. HIV positive patients showed prevalence of (66.70%), whereas HIV-negative patients had (42.60%). Conclusions: The World Health Organization estimated that 26% of patients with TB infection in Nigeria are HIV-positive and the alarming evidence of MDR-TB prevalence in this study calls for close monitoring of the prevalence of drug resistance, especially in HIV-infected population.
Keywords: Human immunodeficiency virus; multidrug-resistant tuberculosis; patient; prevalence; tuberculosis